Determining the costs of delay in the Philippine criminal justice system - Ang, Alvin (Asia-Pacific Social Science Review, 2006)
Criminal justice systems are mostly concerned with dispensing justice accurately rather than the efficiency of the processes involved within the system. With such prioritization, delays become part of the process, which in turn can negatively affect the accused, accuser and society as a whole. While there is an implicit general awareness that delays have costs, there have been few attempts to actually estimate them. However, without such an estimaate, there will be a vague understanding of how big or small its impact is on society.